2016
DOI: 10.1111/jcpe.12501
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells derived from “inflamed” and healthy periodontal ligament tissues and their sheet functionalities: a patient‐matched comparison

Abstract: These data provide additional evidence that I-PDLSCs are functionally compromised compared with H-PDLSCs. Nonetheless, their dominant abundance in the available tissues indicates that stem cells derived from damaged teeth extracted due to periodontitis warrant further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
70
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 46 publications
13
70
2
2
Order By: Relevance
“…The combined data suggest that cell responses to a hypoxic stimulus may vary from cell type to cell type. While previous work indicated that an inflammatory stimulus causes an increased proliferation rate of PDLSCs Tang et al 2016;Zheng et al 2015), such an increase has not been detected in this particular research; our data suggest that the 24-h inflammatory pretreatment has no obvious effect on PDLSC colony formation and proliferation (Fig. 3).…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…The combined data suggest that cell responses to a hypoxic stimulus may vary from cell type to cell type. While previous work indicated that an inflammatory stimulus causes an increased proliferation rate of PDLSCs Tang et al 2016;Zheng et al 2015), such an increase has not been detected in this particular research; our data suggest that the 24-h inflammatory pretreatment has no obvious effect on PDLSC colony formation and proliferation (Fig. 3).…”
Section: Discussioncontrasting
confidence: 81%
“…In parallel, methods for PDLSC isolation and production are developing very quickly, from rapid and safe cell propagation/expansion (Iwata et al 2010;Jung et al 2013;Trubiani et al 2015;Wu et al 2016) to optimal cell material production (Wei et al 2012;Gao et al 2013;Iwata et al 2015). Nevertheless, major challenges still exist, particularly challenges related to producing large numbers of cells from clinically limited PDL tissues and manufacturing/banking robust cell materials, ideally in an off-the-shelf format Tang et al 2016;Wu et al 2016). Great efforts have been and are still being made in this arena to either avoid long-term ex vivo manipulation, maintain cell properties during extensive ex vivo handling and/or modify/engineer cell behavior toward a target purpose (Sharma et al 2011;Thirumala et al 2013).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The effects of different pretreatments on cell immunomodulatory activity were evaluated by detecting the proliferation/apoptosis rate of peripheral blood mononuclear cells (PBMNCs). After co‐culture with pretreated cells, PBMNCs were subjected to analysis of the proliferation/apoptosis rate; the methods for this analysis were described in detail previously . Briefly, density‐gradient centrifugation was used to extracted PBMNCs from fresh blood derived from three systemically healthy donors.…”
Section: Methodsmentioning
confidence: 99%
“…The cell‐to‐cell coordination process required to regenerate the lost periodontium needs stem cell populations that have not been altered by the inflammatory processes that originally destroyed the tissues. Indeed, it has been reported that stem cells from inflamed sites behave differently to those obtained from healthy sites . Regenerative interventions should only be attempted after a health‐associated homeostasis between the host and the resident microbiota has been restored.…”
Section: Future Challengesmentioning
confidence: 99%